Kudeta Dalam Perspektif Hukum Internasional - Souisa, Pelpina Dina Febriska; Rehatta, Veriana Josepha Batseba; Riry, Welly Angela (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Article 33 paragraph (1), 52 of the United Nations Charter and Article 2 paragraph 2 letter (f) of the ASEAN Charter provide space for International Law to be involved in efforts to resolve Dispute Problems (Coup) by using an approach to protecting human rights that involves a State but in fact until now International Law has never participated in efforts to resolve the Government Conflict which was taken through the Coup on the State of Myanmar.Purposes of the Research:To examine or analyze the coup in the perspective of International Law and to examine and discuss the legitimacy or legality of government through a coup.Methods of the Research: The research method used is normative juridical research, the type of research is descriptive analytical. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials used in this research is through literature study. The analysis of legal materials is descriptive qualitative.Research Results: The results showed that: 1). International Law on Change of Government through Coup has never been regulated in detail because it is part of the rights of a State that cannot be interfered with in the internal affairs of its State, but an insistence can be made to become a place of negotiation and mediation for both parties who are fighting for power by using the UN Charter. Article 1, Article 2, Article 33 paragraph 1 and Article 52 as well as the ASEAN Charter Article 1 and Article 2 paragraph 2 letter (f) are related to the Protection of Human Rights. 2). The legality of the government obtained through a coup until now has never been specifically regulated in international law, but when viewed from the point of view of the birth of a country, namely 1. the existence of a government, 2. territory, 3 inhabitants, and 4. recognition from other countries. The legality of the government obtained through the coup d'etat can be said to be valid if it gets recognition from other countries (which in this case is part of (State Politics) in International Relations).